Discussion of Evaluation of the Usefulness to Investors of Different Accounting Estimators of Earnings: A Simulation Approach - Stedry, Andrew C. (Journal of Accounting Research, 1968)
Andrew C. Stedry, Discussion of Evaluation of the Usefulness to Investors of Different Accounting Estimators of Earnings: A Simulation Approach, Journal of Accounting Research, Vol. 6, Empirical Research in Accounting: Selected Studies 1968 (1968), pp. 54-58